Foreign Direct Investment Driven by the Sovereign Wealth Funds and its Impact on the Market Value of the Acquired Companies - Martínek, Stanislav (2019)
The sheer value of the capital allocated in the Sovereign Wealth Funds (SWF), its continuous growth, and its potential to impact global financial markets with direct political and economic consequences sharply contrast with the scarce information on the funds’ financial performance, investment strategies, and overall strategic intentions. This palpable knowledge gap represents the primary motivation behind the research endeavor, whose results are presented in this thesis.Based on an originally collected dataset comprised of the SWFs cross-border investment transactions, we designed a comparative research model to investigate sovereign wealth funds’ long-term impact on the market value of targeted companies. The results signal that the initial positive impact of SWFs on investee performance disappears and the investees tend to underperform the market average in the long run. Next, we employ a comparative analysis of sovereign funds’ real rates of return, and the theoretical returns achievable on assets accumulated in international reserves. The results show that, from 2007 to 2017, sovereign funds’ returns outperformed the theoretical returns of international reserves by almost two percentage points.The last chapter takes the form of a case study that focuses on the influential role SWFs play in supporting national champions in strategic industries. We confirm the unique advantages provided by this model. Despite its economic and political potential, this model involves major risks, especially in times of economic recession, when a substantial government ﬁscal deﬁcit can have a devastating impact on a whole industry and simultaneously lead to severe damage to the international relationships.